High levels of physical activity are associated with poorer asthma control in young females but not in males. Issue 1 (19th November 2015) - Lövström, Ludvig; Emtner, Margareta; Alving, Kjell; Nordvall, Lennart; Borres, Magnus P.; Janson, Christer; Malinovschi, Andrei
Abstract: Background and objective: Earlier studies on the levels of physical activity in asthma patients compared with controls have yielded varying results. We have previously reported that high versus moderate levels of physical activity were associated with higher prevalence of wheezing, especially in females. Here we studied the levels of physical activity in young patients with asthma and healthy subjects and their effect on asthma control. Methods: Four hundred eight physician‐diagnosed patients with asthma and 118 controls (10–34 years) answered questions concerning frequency and/or duration of physical activity and undertook the Asthma Control Test (ACT), spirometry, methacholine challenges and exhaled nitric oxide measurements. Results: Asthma patients were more frequently physically active ( P  = 0.01) and for longer durations ( P  = 0.002) than controls. Highly versus moderately physically active patients with asthma had a higher prevalence of not well‐controlled asthma (ACT < 20) when physical activity was assessed by frequency (40.6% vs 24.1%, P  = 0.001) or duration (39.0% vs 21.7%, P  < 0.001). This was only seen in females who had reduced ACT items ( P  < 0.05). Frequently versus moderately active females had an odds ratio of 4.81 (2.43, 9.51) to have ACT < 20, while no such effect was found in males (OR 1.18 (0.61, 2.30)) and this interaction was statistically significantly associated with gender ( P  = 0.003). No differences in fraction of exhaled nitric oxide or methacholine reactivity were found between moderately and highly physically active females with asthma. Conclusion: Young asthma patients were more active than controls. High levels of physical activity were associated with poor asthma control as judged by the ACT in females, but not in males, and this appears unrelated to airway inflammation or responsiveness. Abstract : Young patients with asthma reported to be more physically active than controls. High versus moderate physical activity levels were associated with poorer asthma control in females, but not in males. This has to be further studied when physical activity is objectively measured and type and intensity of exercise are characterized.